Efektivitas Sistem INSW dalam Sinkronisasi Data Antarinstansi Bea Cukai pada Proses Keagenan Kapal di PT. Samudera Shipping Agency Dumai - Sapa Tamaya Siregar; Syarifur Ridho (Jurnal Bisnis Kreatif dan Inovatif, 2025)
The Indonesia National Single Window (INSW) is an integrated system designed to facilitate, accelerate, and simplify port administration processes through real-time data exchange among relevant agencies. The purpose of this study is to analyze the effectiveness of implementing the INSW system in synchronizing data between customs and other related agencies within the ship agency process at PT. Samudera Shipping Agency Dumai. The research method employed is qualitative, with data collected through library research and field studies. The field study was conducted through direct observation and interviews at PT. Samudera Shipping Agency Dumai, while the library research involved reviewing various related sources, including journals, books, and government regulations. The results of the study indicate that the INSW system makes a significant contribution to harmonizing data between agencies, which positively impacts administrative efficiency, information transparency, and the reduction of data errors, particularly in interactions with customs. The system also supports improved coordination among related parties, such as quarantine offices, harbor masters, and port authorities, thereby enabling more effective services. However, several challenges still hinder optimal performance, including human resource readiness, limited internet connectivity, and dependence on the stability of the central system. These obstacles may lead to technical issues such as system errors, delays in document verification, and even risks of power outages, which could potentially cause delays in data submission and result in sanctions from authorities. In conclusion, the INSW system has proven effective in expediting and simplifying ship agency processes at PT. Samudera Shipping Agency Dumai. Nevertheless, to achieve greater effectiveness, continuous training for human resources, improvement of digital infrastructure, and the development of a more modern, transparent, and internationally competitive system are required.